A taxonomic review of Cuban Eiphosoma Cresson (Hymenoptera: Ichneumonidae), with biogeographical notes - Fernández-Triana, José L.; Ravelo, Horacio Grillo (Zootaxa, 2007)
We revise the Cuban species of Eiphosoma Cresson (Hymenoptera: Ichneumonidae: Cremastinae). Three new species are described: E. bioeco sp. nov., E. dearmasi sp. nov. and E. nelitae sp. nov. All species are assigned to species-groups as defined by Gauld (2000) for the Mesoamerican fauna, and a key to Cuban species is provided. A preliminary analysis of the distribution and faunal similarity for species within the Cuban archipelago is discussed; the Cuban fauna is compared to that of the Caribbean Islands, Florida (USA) and Costa Rica.